2020
DOI: 10.1523/eneuro.0126-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

θ-γ Cross-Frequency Transcranial Alternating Current Stimulation over the Trough Impairs Cognitive Control

Abstract: Cognitive control is a mental process, which underlies adaptive goal-directed decisions. Previous studies have linked cognitive control to electrophysiological fluctuations in the u band and u-g cross-frequency coupling (CFC) arising from the cingulate and frontal cortices. However, to date, the behavioral consequences of different forms of u-g CFC remain elusive. Here, we studied the behavioral effects of the u-g CFC via transcranial alternating current stimulation (tACS) designed to stimulate the frontal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 36 publications
1
22
0
1
Order By: Relevance
“…This is partly due to the heterogeneity of the experimental setups and stimulation sites (frontal, parietal, and occipital) used in these studies. The CFC-tACS protocols have been investigated in several domains (learning, WM, and verbal-long term memory) (Alekseichuk et al, 2016 ; Lara et al, 2018 ; Turi et al, 2020 ; Riddle et al, 2021 ) and have recently gained popularity among the researchers. In principle, the peak-coupled tACS (gamma bursts nested into theta peaks) protocols mimic the endogenous theta-gamma CFC phase specificity needed for cognitive control (Smith et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is partly due to the heterogeneity of the experimental setups and stimulation sites (frontal, parietal, and occipital) used in these studies. The CFC-tACS protocols have been investigated in several domains (learning, WM, and verbal-long term memory) (Alekseichuk et al, 2016 ; Lara et al, 2018 ; Turi et al, 2020 ; Riddle et al, 2021 ) and have recently gained popularity among the researchers. In principle, the peak-coupled tACS (gamma bursts nested into theta peaks) protocols mimic the endogenous theta-gamma CFC phase specificity needed for cognitive control (Smith et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, theta-gamma tACS boosted working memory more than theta-tACS alone, and the effect was more pronounced when the gamma bursts (in the range of 80–100 Hz) were over the peak of the theta cycles (peak-coupled tACS). Alekseichuk et al ( 2016 ) and Turi et al ( 2020 ) investigated the effect of theta/gamma CFC tACS protocols aimed at the stimulating frontal and cingulate cortices on Go/NoGo monetary reward-based and punishment-based instrumental learning task outcomes. They used different theta/gamma CFC tACS protocols, in contrast to the results of (Alekseichuk et al, 2016 ) This study showed no consistent reinforcement effect of peak-coupled tACS, whereas trough-coupled tACS (gamma bursts were nested into theta troughs) impaired cognitive control (Alekseichuk et al, 2016 ; Turi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to tACS, which uses a single-frequency stimulation (e.g., 10 Hz for alpha-band stimulation), NFB protocols usually train the whole bandwidth (e.g., the whole alpha bandwidth 8–13 Hz up). In multifrequency protocols, the NFB research field contains many studies using multifrequency protocols (Peniston and Kulkosky, 1991 ; Egner et al, 2002 ; Dohrmann et al, 2007 ; Friedrich et al, 2015 ; Vanneste et al, 2016 ; Güntensperger et al, 2019 ) whereas the multifrequency protocols in tACS seem to be quite an emerging field of research with a much shorter history than multifrequency NFB protocols (Helfrich et al, 2016 ; Lara et al, 2018 ; Bramson et al, 2020 ; Turi et al, 2020 ).…”
Section: Mechanisms Of Tacs and Nfbmentioning
confidence: 99%
“…While NFB works on the principle of self-regulation of endogenous EEG activity (Enriquez-Geppert et al, 2017;Ros et al, 2020), tACS is based on delivering external electric fields capable of interacting with an ongoing EEG activity (Liu et al, 2018;Vöröslakos et al, 2018). Despite the vast differences in mechanisms of action of tACS and NFB, according to the thorough research, both methods can successfully modulate various EEG bands (Lubar, 1997;Weber et al, 2011;Staufenbiel et al, 2014;Witkowski et al, 2016;Violante et al, 2017;Wischnewski and Schutter, 2017;Pimenta et al, 2018;Tseng et al, 2018;Abellaneda-Pérez et al, 2020). Both neuromodulatory methods have been also investigated in their ability to improve various brain functions such as motor performance (Joundi et al, 2012;Ros et al, 2014b;Scharnowski et al, 2015;Moisa et al, 2016;Guerra et al, 2018Guerra et al, , 2019Bologna et al, 2019), memory processes (Alexeeva et al, 2012;Polanía et al, 2012;Violante et al, 2017;Dobrakowski and Łebecka, 2020), attention (Escolano et al, 2014;Hopfinger et al, 2017;Berger and Davelaar, 2018;Deiber et al, 2020), creativity (Gruzelier, 2009;Agnoli et al, 2018;Di Bernardi Luft et al, 2018), emotional regulation (Johnston et al, 2010;Bramson et al, 2020), etc.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that decreased resting-state theta–gamma PAC may be a biomarker of poorer mental health (specifically depression) and that lasting changes in PAC may be a mechanism underlying TMS treatment. Notably, cross-frequency theta–gamma tACS protocols have been demonstrated to influence memory ( Alekseichuk et al, 2016 ; Lara et al, 2018 ), cognitive control ( Turi et al, 2020 ), and emotional-action control ( Bramson et al, 2020 ). Alekseichuk et al (2016) reported that theta–gamma tACS has a greater effect on working memory than theta tACS.…”
Section: Pac Neurostimulation and Mental Healthmentioning
confidence: 99%